1999
DOI: 10.1029/1999jd900332
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of stratospheric tracers using an improved empirically based two‐dimensional model transport formulation

Abstract: Abstract. We have developed a new empirically based transport formulation for use in our Goddard Space Flight Center (GSFC) two-dimensional chemistry and transport model. In this formulation, we consider much of the information about atmospheric transport processes available from existing data sets. This includes zonal mean temperature, zonal wind, net heating rates, and Eliassen-Palm flux diagnostics for planetary and synoptic-scale waves. We also account for the effects of gravity waves and equatorial Kelvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 56 publications
1
74
0
Order By: Relevance
“…CH 4 , exhibit distributions that are well correlated and vary seasonally in response to changes in the BDC (Plumb and Ko, 1992;Holton, 1986). Figure 2 is an example of the zonally averaged distribution of CH 4 for January from a NASA/Goddard, two-dimensional chemistry and transport model simulation (Fleming et al, 1999). The white arrows show the effects of the stratospheric BDC, which is strong in the winter hemisphere (longer arrows) and weak in the summer stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 , exhibit distributions that are well correlated and vary seasonally in response to changes in the BDC (Plumb and Ko, 1992;Holton, 1986). Figure 2 is an example of the zonally averaged distribution of CH 4 for January from a NASA/Goddard, two-dimensional chemistry and transport model simulation (Fleming et al, 1999). The white arrows show the effects of the stratospheric BDC, which is strong in the winter hemisphere (longer arrows) and weak in the summer stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…This model was first discussed over 20 yr ago (Douglass et al, 1989;Jackman et al, 1990) and has undergone extensive improvements over the years (e.g., Considine et al, 1994;Jackman et al, 1996;Fleming et al, 1999Fleming et al, , 2007Fleming et al, , 2011. The vertical range of the model, equally spaced in log pressure, is from the ground to approximately 92 km (0.0024 hPa) with a 1 km grid spacing.…”
Section: Description Of the Gsfc 2-d Modelmentioning
confidence: 99%
“…3.5. The model's 2-D transport is prescribed based on calculations by Fleming et al (1999) for each year from 1978 to 2004, employing observed temperature, ozone, water vapor, zonal wind, and planetary waves. Different phases of the quasi-biennial oscillation (QBO) are included in the observational data employed.…”
Section: Aerosol Modelmentioning
confidence: 99%